Adenoma size and postoperative IGF-1 levels predict surgical outcomes in acromegaly patients: results of the Swiss Pituitary Registry (SwissPit) - Julia Kempf; Alexander Schmitz; Aline Meier; Neele Delfs; Beat Mueller; Javier Fandino; Philipp Schuetz; Sven Berkmann (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY